The Relationship of Individual Characteristics, Work Stress and Work Fatigue with Patient Safety Culture at X Hospital, East Tanjung Jabung Regency in 2025 - Agusnawati, Agusnawati; Guspianto, Guspianto; Asparian, Asparian; Amir, Andy; Kalsum, Ummi; Eka Rini, Willia Novita; Muldiasman, Muldiasman (Rifa'Institute, 2026)
Introduction: Patient safety is a fundamental component of hospital service quality and is strongly influenced by patient safety culture. Various individual factors, including demographic characteristics, job stress, and work-related fatigue, are considered to play an important role in shaping patient safety culture in hospitals. Objective: The study population consisted of all hospital staff, both clinical and non-clinical, with a total sample of 197 respondents selected using proportional random sampling. Method: This study employed an observational analytic design with a cross-sectional approach. Result and Discussion: showed that patient safety culture at RSUD X, Tanjung Jabung Timur Regency, was predominantly in the low category. Bivariate analysis indicated a significant relationship between gender and patient safety culture, while age, education level, employment status, length of work, job stress, and work fatigue were not significantly associated with patient safety culture. Multivariate analysis revealed that gender was the most dominant factor associated with patient safety culture. Conclusions: patient safety culture at RSUD X still requires improvement, and gender is the most influential individual factor related to patient safety culture